2016
DOI: 10.1111/acer.13133
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Vapor Inhalation as a Model of Alcohol‐Induced Organ Disease

Abstract: Background Chronic intermittent ethanol vapor exposure (CIEV) has been used extensively to produce rodent models of alcohol dependence, but unlike other models of alcohol abuse, CIEV has not been assessed as a model of end-organ damage. The purpose of this study was to characterize the effects of CIEV on peripheral organ systems affected by alcohol abuse, including the liver, lungs and cardiovascular system. Methods Adult male Sprague-Dawley rats were exposed to daily CIEV for a period of 8 weeks (14HR ON/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…Importantly, animals do not lose significant body weight (defined as >10%). In addition, the effects of ethanol vapor on lungs, heart, and liver are comparable to those associated with other chronic ethanol exposure models (Mouton et al, 2016 ).…”
Section: Methodssupporting
confidence: 66%
“…Importantly, animals do not lose significant body weight (defined as >10%). In addition, the effects of ethanol vapor on lungs, heart, and liver are comparable to those associated with other chronic ethanol exposure models (Mouton et al, 2016 ).…”
Section: Methodssupporting
confidence: 66%
“…This discrepancy in hepatic PCSK9 levels could be attributed to distinct animal protocols of different duration specific for investigating different stage of ALD in 2 different species. Although blood alcohol levels in the vapored rats were maintained high, raning between 150 and 250 mg% 33 , plasma ALT and cytochrome P450 2E1 (CYP2E1, a marker for alcohol liver injury) showed a 2-fold increase in the alcohol-exposed group compared to the control group 67 . On the other hand, plasma ALT and AST were 4-fold elevated and hepatic CYP2E1 was remarkably upregulated in the group feeding chronic-plus-single-binge (binge alcohol-fed group) compared to a control group.…”
Section: Discussionmentioning
confidence: 93%
“…Ethanol vapor levels were set to achieve blood alcohol levels (BALs) of 150–200 mg/dl. We have previously shown that chronic ethanol administration at this BAL produced end organ damage including markers of hepatic injury and inflammation, decreases in left ventricular wall thickness, increases in systolic blood pressure, and pulmonary inflammatory cell infiltration (Mouton et al, 2016a). BALs were assessed from tail vein blood samples using an Analox GM7 analyzer (London, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol is among the most commonly abused drug worldwide, and as such, chronic alcohol abuse creates an enormous economic burden on the healthcare system (Hasin et al, 2007). Chronic alcohol abuse has many health implications that affect multiple organ systems, including the heart (Mouton et al, 2016a, Piano, 2002). Alcoholic cardiomyopathy (ACM) is a term used to describe a dilated cardiomyopathy that is associated with chronic alcohol consumption (Piano, 2002).…”
Section: Introductionmentioning
confidence: 99%